Bank capital regulation, the lending channel and business cycles - Longmei Zhang (Deutsche Bundesbank, 2009)
This paper develops a Dynamic Stochastic General Equilibrium (DSGE) model to study how the instability of the banking sector can amplify and propagate business cycles. The model builds on Bernanke, Gertler and Gilchrist (BGG) (1999), who consider credit demand friction due to agency cost, but it deviates from BGG in that financial intermediaries have to share aggregate risk with entrepreneurs, and therefore bear uncertainty in their loan portfolios. Unexpected aggregate shocks will drive loan default rate away from expected, and have an impact on both firm and bank's balance sheet via the financial contract. Low bank capital position can create strong credit supply contraction, and have a significant effect on business cycle dynamics.
Keywords: E32; E44; E52; 330; Bank capital regulation; banking instability; financial friction; business cycle; Eigenkapitalvorschriften; Bankrisiko; Kreditmarkt; Marktversagen; Kreditrisiko; Kreditrationierung; Akzelerator; Konjunktur; Finanzmarktkrise; Wirtschaftskrise; Theorie